Convenient Unsymmetrical Disulfane Synthesis: Basic Zeolite‐Catalyzed Thiol‐Disulfane Exchange Reaction. Issue 22 (8th October 2021) - Yamamoto, Eiji; Kawai, Yasutaka; Takakura, Kei; Kimura, Moemi; Murayama, Haruno; Matsueda, Hironobu; Otsuki, Shujiro; Sakata, Hiroshi; Tokunaga, Makoto
Abstract: Convenient catalytic synthetic methods for the preparation of unsymmetrical disulfanes are described. Na‐exchanged X type zeolite (Na‐X), commercially available as MS‐13X, effectively catalyzes thiol‐disulfane exchange reactions with 1.0 equivalent of thiols and 2.5–3.0 equivalents of disulfanes at 10 °C to room temperature under air. The reactions of sterically‐hindered disulfanes or electron‐deficient thiol substrates require high temperatures under inert atmospheres to maintain the good product yields. Various functionalized thiols and disulfanes are tolerant in the present catalytic systems, affording the corresponding unsymmetrical disulfanes in good‐to‐high yields (up to 96 %). The Na‐X catalyst was successfully recycled 10 times without loss of yield. Preliminary mechanistic studies suggest the involvement of base‐catalyzed SN 2‐S displacement and/or addition‐elimination mechanisms, assisted by hydrogen‐bonding interactions. Abstract : Na‐exchanged X type zeolite, commercially available as MS‐13X, effectively catalyzes thiol‐disulfane exchange reactions under aerobic mild conditions to give the unsymmetrical disulfanes in good‐to‐high yields. Various thiols and disulfanes are tolerant in the catalytic systems. Preliminary mechanistic studies suggest the involvement of base‐catalyzed SN 2‐S displacement and/or addition‐elimination mechanisms assisted by H‐bonding interactions.